Congenital heart disease and pregnancy: A contemporary approach to counselling, pre-pregnancy investigations and the impact of pregnancy on heart function. (June 2017) - Cauldwell, Matthew; Gatzoulis, Michael; Steer, Philip
Cardiac disease in pregnancy is a challenging clinical problem. The number of women pursuing pregnancy and the underlying complexity of their cardiac disease is increasing, such that heart disease is now the leading cause of maternal mortality in developed countries. Women with congenital heart disease make up the majority of these cases and although maternal mortality is infrequent, a good outcome is only achieved though meticulous multidisciplinary care, beginning with pre-pregnancy counselling. All women with congenital heart disease should be assessed and be referred for pre-conception counselling prior to pregnancy and should receive thorough clinical assessment prior to pregnancy. In some conditions, such as pulmonary hypertension or severe/progressive aortic dilatation, pregnancy is of very high risk and women should be made aware of such risks. In such circumstances, if women choose to proceed with pregnancy, it is paramount that they are cared for by multidisciplinary teams who have experience and expertise of managing such conditions to minimise risks and optimise outcome.